DOSE DEPENDENT EFFECT ON HYPOGLYCEMIC AND ANTIHYPERGLYCEMIC ACTIVITIES OF CHLOROFORM EXTRACT OF PHYSALIS MINIMA IN STREPTOZOTOCIN INDUCED DIABETIC RATS - Putta, Swathi; Chedalawada, Vijay (International Journal of Current Pharmaceutical Research, 2014)
This study was undertaken to investigate the effect of chloroform extract of Physalis minima (CPM) whole plant on blood glucose levels and other biochemical parameters in streptozotocin (55 mg/kg. b. w., i. p) induced diabetic rats. The treatment was given at doses of (200, 300 and 400mg/kg. b. w., p. o), for 28 days. After the treatment with there is a significant reduction was observed in fasting blood glucose levels in treated diabetic rats. The CPM showed considerable lowering effect of total cholesterol, triglycerides, LDL & VLDL levels and considerably increase HDL cholesterol levels. There is a significant reduction of the SGOT, SGPT and ALP levels in diabetic rats treated with CPM, compared with disease control group. These results suggest that Physalis minima possesses antidiabetic activity in streptozotocin induced diabetic rats.